Improving BIM asset and facilities management processes: A Mechanical and Electrical (M&E) contractor perspective. (November 2020) - Jang, Ryan; Collinge, William
Abstract: Despite BIM asset information management processes having advanced to globally recognised standards, facilities and asset integration remains problematic for many companies engaged in the construction project lifecycle. Challenges typically stem from deficiencies in the BIM regulations and standards, inaccurate information exchanges, software interoperability issues and unclear requirement definitions that ultimately result in higher project costs and poorer operational efficiencies. An exploration of these challenges and their potential solutions is therefore important if BIM-FM integration issues are to be improved. Few studies have systematically investigated this subject from the perspective of a BIM-accredited Mechanical and Electrical (M&E) company engaged on projects. This paper combines a literature review with an empirical case study of a BIM-accredited Mechanical and Electrical (M&E) contractor to explore the critical issues surrounding facilities and asset management integration; this combination of evidence providing a distillation of the issues surrounding BIM/FM asset integration and its' resolution. 15 key issues from the literature were classified under 4 broad themes (Informational, Technological, Organisational and Industrial) as being of primary concern; the case study analysis verifying the findings and also providing a series of bespoke recommendations for improving industry practice. The paper clarifies the problem issues (both negotiable and systemic) afflicting the industry, indicating how individual companies can develop their own processes for improving BIM-based asset integration. It may be concluded that although BIM asset integration processes have reached globally recognised standards, systemic characteristics of the industry result in persisting problems that impact the BIM-FM asset management journey. Highlights: Reviews BIM asset management work from perspective of a Mechanical and Electrical (M&E) company. Comprehensive literature review identifies 15 issues under 4 concepts impacting effective asset management. Empirical case study analysis provides practitioner insights and recommendations to improve practice. Presents a series of bespoke BIM processes to address deficiencies in the BIM asset management work stream. Clarifies how PAS 1192–2 and ISO 19650–2 may be supplemented for an M&E company.